2022
DOI: 10.3389/fpsyg.2022.745580
|View full text |Cite
|
Sign up to set email alerts
|

Culture as a Moderator of Epistemically Suspect Beliefs

Abstract: A consistent finding reported in the literature is that epistemically suspect beliefs (e.g., paranormal beliefs) are less frequently endorsed by individuals with a greater tendency to think analytically. However, these results have been observed predominantly in Western participants. In the present work, we explore various individual differences known to predict epistemically suspect beliefs across both Western and Eastern cultures. Across four studies with Japanese (n = 666) and Western (n = 650) individuals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
3
12
1
Order By: Relevance
“…These beliefs tend to be correlated (Lindeman & Svedholm, 2012;Lobato et al, 2014) and they often share similar psychological antecedents (Čavojová et al, 2019;Erceg et al, 2019;Šrol, 2022). More importantly given the present topic, there are a large number of studies showing that intuitive people tend to hold more epistemically suspect beliefs in several cultures (e.g., Ballová Mikušková & Čavojová, 2020; Bouvet & Bonnefon, 2015;Gervais, 2015;Majima, 2015;Pennycook, Cheyne, et al, 2012Pennycook, McPhetres, et al, 2021;Pennycook, Bago, et al, 2022;Shtulman & McCallum, 2014;Šrol, 2022;Ståhl & van Prooijen, 2018;Svedholm & Lindeman, 2013;Swami et al, 2014;Toplak & Flora, 2021;van Elk, 2019;van Prooijen et al, 2022) (but see Majima et al, 2022). To simplify the summary of these findings, I will break these epistemically suspect beliefs into five categories that represent most (but not all) of the research on the topic relating to analytic thinking.…”
Section: Epistemically Suspect Beliefsmentioning
confidence: 80%
“…These beliefs tend to be correlated (Lindeman & Svedholm, 2012;Lobato et al, 2014) and they often share similar psychological antecedents (Čavojová et al, 2019;Erceg et al, 2019;Šrol, 2022). More importantly given the present topic, there are a large number of studies showing that intuitive people tend to hold more epistemically suspect beliefs in several cultures (e.g., Ballová Mikušková & Čavojová, 2020; Bouvet & Bonnefon, 2015;Gervais, 2015;Majima, 2015;Pennycook, Cheyne, et al, 2012Pennycook, McPhetres, et al, 2021;Pennycook, Bago, et al, 2022;Shtulman & McCallum, 2014;Šrol, 2022;Ståhl & van Prooijen, 2018;Svedholm & Lindeman, 2013;Swami et al, 2014;Toplak & Flora, 2021;van Elk, 2019;van Prooijen et al, 2022) (but see Majima et al, 2022). To simplify the summary of these findings, I will break these epistemically suspect beliefs into five categories that represent most (but not all) of the research on the topic relating to analytic thinking.…”
Section: Epistemically Suspect Beliefsmentioning
confidence: 80%
“…1 These three types of EUB are progressively getting more attention from researchers and governments, probably due to the combination of their (1) high social prevalence and (2) negative implications. Regarding the first point, paranormal, pseudoscientific and conspiracy beliefs are common in the general population around the world (e.g., Höllinger & Smith, 2002; Imhoff et al, 2022; Majima et al, 2022), Spain being no exception (e.g., Díaz‐Vilela & Álvarez‐González, 2004; Imhoff et al, 2022; Torres et al, 2020). Regarding the second point, these three types of EUB are associated with negative outcomes such as interference with critical thinking, increased vulnerability to deception, rejection of science and objectivity, institutional distrust, decreased political and social engagement, social polarization and intolerance (e.g., increased prejudice, discrimination and intergroup violence), increased health risks (e.g., ignoring/rejecting health guidelines, opportunity costs of choosing ineffective treatments, iatrogeny) or failure to carry out constructive problem‐solving behaviors (Fasce, 2018; Irwin, 2009; Jolley et al, 2020; Stone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… In the context of paranormal, pseudoscientific and conspiracy beliefs, alternative nomenclatures to EUB have also been used, such as epistemically suspect beliefs (e.g., Majima et al, 2022), scientifically unsubstantiated beliefs (e.g., Stone et al, 2018), scientifically unaccepted beliefs (e.g., Irwin & Marks, 2013), and contaminated mindware (e.g., Rizeq et al, 2020). …”
mentioning
confidence: 99%
“…Nevertheless, the predisposition to acquire scientific knowledge itself could be modulated by cognitive and meta-cognitive factors related to reasoning styles and analytic thinking. In relation to this, Fasce and Picó (2019) observed that the presence of pseudoscientific beliefs correlated with scores on the Rational-Experiential Information Styles selfreport questionnaire (Epstein, et al, 1996; see also Majima et al, 2022 for similar results with an abbreviated version of the scale). Specifically, endorsement of pseudoscience among Fasce and Picó's participants was positively correlated with scores on the faith in intuition subscale (i.e., the extent to which and individual relies on intuitive thinking), and negatively associated with scores on the need for cognition subscale (i.e., the individuals' level of enjoyment and engagement of rational, logical, and analytic thinking).…”
mentioning
confidence: 64%
“…Among other factors, discrepancies between the results of these studies might be related to the use of self-report measures, which might not be the best tool to adequately capture reasoning strategies. In this sense, Fasce and Picó (2019; see also Majima et al, 2022) confirmed their results with regard to analytical thinking by means of the Cognitive Reflection Test (CRT; Frederick, 2005). Correct responses in this questionnaire have been assumed to indicate the ability to resist reporting intuitive answers ("System 1"-based responses in terms of Stanovich and West, 2000), and engage in reflective, effortful reasoning ("System 2"-based processes).…”
mentioning
confidence: 72%